2022
DOI: 10.1101/2022.08.25.22279205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intentions to get vaccinated against Monkeypox in Healthcare workers in France and Belgium correlates with attitudes toward COVID-19 vaccination

Abstract: Background: Front-line healthcare workers (HCWs) could be at-risk for Monkeypox infections. Vaccine hesitancy also affects HCWs and has an impact on their own attitudes toward vaccination. In the context of the exhaustion due to COVID-19 pandemic, we aimed to evaluate intentions to get vaccinated against Monkeypox in HCWs in France and Belgium. Methods: We performed a cross-sectional study (snowball sampling) using a self-administered on-line questionnaire to evaluate intentions to get vaccinated against Monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(13 reference statements)
1
3
1
1
Order By: Relevance
“…That is, most people indicated a high probability of being vaccinated against Monkeypox. This agrees with what has been reported in other studies conducted in different cultural contexts where between 46% and 72% of participants were likely to agree to be vaccinated against Monkeypox (15)(16)(17). One of the factors that may have contributed to this result is that most of the participants had previously been vaccinated against COVID-19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…That is, most people indicated a high probability of being vaccinated against Monkeypox. This agrees with what has been reported in other studies conducted in different cultural contexts where between 46% and 72% of participants were likely to agree to be vaccinated against Monkeypox (15)(16)(17). One of the factors that may have contributed to this result is that most of the participants had previously been vaccinated against COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Intention to vaccinate involves willingness and acceptability to vaccinate, as well as positive attitudes toward the vaccine administered, as opposed to resistance or refusal to vaccinate (14). A recent survey of health care workers indicated that 55.4% were likely to receive the Monkeypox vaccine and 79% would accept it if it were recommended to the general population (15). Another study with a U.S. sample indicated that 46% would receive a Monkeypox vaccine if it were recommended to them, 29% would refuse to receive it, while 25% were hesitant (16).…”
Section: Original Introductionmentioning
confidence: 99%
“…In this study, the finding of an Mpox vaccine acceptance rate of only 29% is lower compared to the pooled estimate in a recent meta-analysis that involved HCWs surveyed in four different studies showing an acceptance rate of 63% [ 43 , 56 , 79 , 80 , 81 ]. Additionally, a recent review by Lounis and Riad pointed to the issue of possible Mpox vaccination hesitancy among health professionals despite the higher rates of vaccine acceptance compared to the rates reported among the general public worldwide [ 57 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Of these, 105 articles remained after eliminating 197 duplicate records. Finally, a careful assessment of the complete texts found 11 studies that fully complied with the eligibility criteria [33][34][35][36][37][38][39][40][41][42][43]. The detailed flow chart of the literature selection is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%